Electronic transport through a quantum ring coupled to ferromagnetic leads - 迟锋 孙连亮 黄玲 赵佳 (Chinese physics B, 2011)
We study the spin-dependent transport through a one-dimensional quantum ring with taking both the Rashba spin-orbit coupling （RSOC） and ferromagnetic leads into consideration. The linear conductance is obtained by the Green＇s function method. We find that due to the quantum interference effect arising from the RSOC-induced spin precession phase and the difference in travelling phase between the two arms of the ring, the conductance becomes spin-polarized even in the antiparallel magnetic configuration of the two leads, which is different from the case in single conduction channel system. The linear conductance, the spin polarization and the tunnel magnetoresistance are periodic functions of the two phases, and can be efficiently tuned by the structure parameters.